A Suitable One-Pot Synthesis of 3,4-Dihydropyrano[3,2-c]Chromenes Using Magnetic Nanoparticles Tag: Piperidinium Benzene-1,3-Disulfonate Ionic Liquid as a Novel, Green, Efficient and Reusable Catalyst in Aqueous Medium - Ghorbani-Vaghei, Ramin; Mahmoodi, Jafar; Maghbooli, Yaser; Shahriari, Azadeh (Current Organic Synthesis, 2017)
Background: The synthesis of 3,4-dihydropyrano[3,2-c]chromenes via the one-pot three-component reactions of various aldehydes, malononitrile, and 4-hydroxycumarin at 60 °C in water as a solvent by the magnetic nanoparticles tag: piperidinium benzene-1,3-disulfonate ionic liquid as a green and efficient catalyst. Some benefits of the presented technique are significant cost impact, impressive catalysis and the ability to reuse of the catalyst. The current procedure offers high yield, short reaction times, neat reaction and simple reusable catalyst. Objective: A magnetic nanoparticles tag: piperidinium benzene-1,3-disulfonate ionic liquid as a green, efficient, reusable and heterogeneous catalyst was used for the synthesis of 3,4-dihydropyrano[3,2-c]chromenes. Method: We have described an efficient and green process for the synthesis of the one-pot three-component synthesis of 3,4-dihydropyrano[3,2-c]chromenes from the reaction between 4-hydroxy-coumarin with malononitrile and aldehydes in the presence of catalytic amount of magnetic nanoparticles tag: piperidinium benzene-1,3-disulfonate ionic liquid as a novel and powerful nano ionic liquid with good to excellent yields and in a short reaction time in water solvent at 60 °C. Result: The main advantage of this process is the simplicity of the work-up and the products can be isolated without chromatography. Conclusion: We suggest that the method has also various additional advantages such as low loading of catalyst, clean reaction, which makes it a suitable and noteworthy approach for the synthesis of 3,4- dihydropyrano[3,2-c]chromenes.
Keywords: 4-Dihydropyrano[3